Electrospun PVDF-Ag@AgCl Porous Fiber Membrane: Stable Anti-Foul and Antibacterial Surface. Issue 3 (2nd August 2020) - Tian, Ying; Shu, You; Zhang, Xiaomin; Mahmud, Sakil; Zhu, Jin; Su, Shengpei
Abstract : The formation of membrane fouling in the process of wastewater treatment is a significant challenge. Here, we present a novel strategy to design a filtration membrane with efficient antifouling property by one-pot electrospinning of silver chloride and dimethylformamide (AgCl2 − /DMF) solution. The AgCl in the porous polyvinylidene difluoride (PVDF) fiber was partly reduced into Ag 0 to form Ag@AgCl after light irradiation. Nanoporous structure of the PVDF-Ag@AgCl electrospun fibers was obtained and adjusted by controlling the water content in the solution, which was also affected by the concentration of sodium chloride (NaCl) and silver nitrate (AgNO3 ). Thereafter, the prepared PVDF-Ag@AgCl nanoporous fiber membrane exhibited excellent and stable antifouling efficiency in terms of photodegradation effect on methyl orange (more than 80% degradation even after three times of recycling), antibacterial ability (2.1–2.4 mm zone of inhabitation) and flux permeability recovery toward bovine serum albumin (BSA) in the process of recycling (about 93% by 40 min in first cycles and 62% in the third cycles).Hence, the as-prepared membrane is found to be a multifunctional composite with high potential in the field of wastewater treatment.